Claiming the corner office: Female CEO careers and implications for leadership development. Issue 2 (14th December 2017) - Athanasopoulou, Andromachi; Moss‐Cowan, Amanda; Smets, Michael; Morris, Timothy
Abstract : Drawing on evidence from a unique data set of in‐depth qualitative interviews with 12 female CEOs (and 139 male CEOs) of global corporations, we explore what enables some women to become CEOs. By drawing on our data from male and female CEOs, we set the scene by comparing the advice they would give to young women as they start their careers. We then focus the rest of our article on the experiences and career trajectory of the 12 female CEOs. We make three theoretical contributions: We identify, at the individual level, how women can take active ownership of their careers as part of a self‐acceptance process; how they can embrace gynandrous leadership as part of a self‐development process where both feminine and masculine leadership behaviors are embraced, with the feminine being dominant to help move beyond gender stereotypes, and finally, how they translate leadership —rather than combine—gender‐based behaviors as part of a self‐management process to develop their unique leadership style. For each of these theoretical contributions at the individual level, we also provide two practical recommendations for HR practice and policy, one relating to the intraorganizational context and the second having institutional‐level implications. We conclude by discussing implications for future research.